The Sanctity and Value of Human Life in Contemporary Times: A Reflection on Genocides - Fazeel Eayaz; Thameem Ushama (International Research Journal of Arabic and Islamic Studies, 2024)
This article explores the profound concept of the sanctity and value of human life through the lens of contemporary genocides and mass atrocities. It underscores the disparity between the fundamental principle that every human life is sacred and the ongoing disregard for this principle evidenced by conflicts and genocides in regions such as Gaza, Ukraine, Myanmar, China, and beyond. The article provides a comprehensive analysis of the sanctity of human life, tracing its ethical, moral, and legal foundations across various religious and philosophical traditions. It critically examines recent genocides, including the Rohingya crisis in Myanmar, the repression of Uighurs in China, the Tigray conflict in Ethiopia, and the persistent violence in Gaza and Ukraine. The discussion delves into the complex interplay of ethnic hatred, political power struggles, and economic factors that drive these atrocities, highlighting the roles of dehumanization and propaganda in facilitating violence. The article also evaluates the effectiveness of international responses, including interventions by the United Nations and the International Criminal Court, and reflects on their successes and shortcomings. It emphasizes the moral and ethical responsibilities of individuals, communities, and nations in preventing genocides, advocating for a collective commitment to the principle of "Never Again." The importance of education and awareness in fostering a culture that values human life and combats hatred is highlighted, with recommendations for integrating lessons on human rights and genocides into curricula and promoting media literacy. The article concludes by reaffirming the need for proactive measures and a global effort to uphold human dignity, calling for continued vigilance and compassion to prevent future atrocities and build a world where every human life is respected and protected.